Development and psychometric properties of the Suicidality: Treatment Occurring in Paediatrics (STOP) Suicidality Assessment Scale (STOP-SAS) in children and adolescents - Flamarique, Itziar; Dittmann, Ralf (BMC pediatrics, 2016)
To create a self-reported, internet-based questionnaire for the assessment of suicide risk in children and adolescents.